2022
DOI: 10.3390/su142215422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sustainability of New Construction Projects over Time by Examining the Evolution of the LEED Rating System

Abstract: In 1998, the U.S. Green Building Council (USGBC) developed the Leadership in Energy and Environmental Design (LEED) program to provide a standard form of evaluation for sustainability in building design and construction. Since its inception, LEED has undergone seven significant revisions, wherein the expectations needed to achieve the desired certification level were clarified and updated. The reasons for these updates are varied and include the recognition of new technologies and materials, the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, there is an upward trend in the level of LEED certification attained by buildings [95]. According to Madson et al [103], achieving higher certification levels in newer versions of LEED has become more challenging. The authors emphasized that regardless of the method used, converted LEED scores showed a positive correlation with time, suggesting that the sustainability of buildings has increased from 2006 to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is an upward trend in the level of LEED certification attained by buildings [95]. According to Madson et al [103], achieving higher certification levels in newer versions of LEED has become more challenging. The authors emphasized that regardless of the method used, converted LEED scores showed a positive correlation with time, suggesting that the sustainability of buildings has increased from 2006 to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…LEED 4.0. released in 2013, focused on performance-based metrics, including lifecycle assessment, with an increased emphasis on materials and resources. LEED version 4.1, released in 2019, incorporated changes to streamline the certification process and encourage higher levels of sustainability performance [57]. Unlike BREEAM, LEED was originally designed to reward energy saving measures rather than a direct reduction in energy use.…”
Section: Building Regulations and Rating Systems In Kenyamentioning
confidence: 99%
“…In 2000, the American Association of State Highway and Transportation Officials (AASHTO) published a constructability review of best practices guide [46]. The work presented in this guide emphasized the importance of implementing a CR program due to its numerous benefits.…”
Section: Constructability Reviewsmentioning
confidence: 99%